2018
DOI: 10.1259/dmfr.20170345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of natural mandibular shape asymmetry: an approach by using elliptical Fourier analysis

Abstract: The mandibular asymmetry by shape is present in all patients and should not be articulated exclusively to pathological processes, therefore, along with sexual dimorphism and differences between skeletal classes must be taken into account for improving mandibular prediction systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A further limitation of this study is that by design, this method is limited to two-dimensional shape prediction based on two-dimensional radiographic imaging, whereas the mandible is a complex three-dimensional object [ 12 ]. Transverse measurements such as bigonial width or any asymmetries [ 13 ] could not be assessed using this methodology. Three-dimensional imaging with further landmarks, measurements and volumetric data would be required in order to assess more complex differences in shape, size and position.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation of this study is that by design, this method is limited to two-dimensional shape prediction based on two-dimensional radiographic imaging, whereas the mandible is a complex three-dimensional object [ 12 ]. Transverse measurements such as bigonial width or any asymmetries [ 13 ] could not be assessed using this methodology. Three-dimensional imaging with further landmarks, measurements and volumetric data would be required in order to assess more complex differences in shape, size and position.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 6 7 8 9 ] Furthermore, condylar asymmetries are believed to be among the most potent causes of mandibulofacial asymmetries. [ 10 11 12 ] Studies have shown that if asymmetries are not treated in growing patients, mandibular displacement can change the amount and severity of force applied to both the mandible and TMJ. [ 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the exact morphology of the normal mandible before disease is often difficult to obtain because the mandible is already deformed when the doctor first examines it. Additionally, the human mandible has strong specificity, and its morphology varies between individuals [5][6][7][8][9] , making it impossible to use a universal mandibular model as a reference for surgery 10 and increasing the uncertainty of the surgical effect.…”
Section: Introductionmentioning
confidence: 99%